Improvement of dissolution properties of albendazole fromdifferent methods of solid dispersion - Helal Uddin, A.B.M.; Azad, A.K; Jahan, K; Sathi, T.S.; Sultana, R; Abbas, Syed A (2018)
Poor aqueous solubility of drugs results in poor absorption and bioavailability. The objective of solid dispersion technology is to increase the dissolution properties of highly lipophilic drugs, by using different hydrophilic carriers thereby improving their bioavailability. This technology is useful for enhancing the dissolution, absorption and therapeutic efficacy of drugs in dosage forms. Albendazole is a broad-spectrum antihelmintic agent used for the treatment of a variety of parasitic worm infestations. It is practically insoluble in water but slightly soluble in solvents like chloroform, methanol, ethyl acetate, and acetonitrile. The aim of our study was to improve the dissolution profile of albendazole using HPMC K 100 LV, Kollidon VA64 and Mannitol as carriers by solid dispersion techniques. From the prepared solid dispersion, formulation code CSF5 showed better result where carrier was HMPC K 100 LV at 1:10 ratio in solvent evaporation method. The HPMC K 100 LV showed better result for both kneading and solvent evaporation methods. Moreover, among the method employed, solvent evaporation method showed better solubility of drug at 60 min also at 1:10 ratio which was 78.86%. Results indicated that current formulation of solid dispersion is a promising approach for enhancing drug solubility and dissolution.